2011
DOI: 10.1590/s1806-83242011000600015
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the microhardness of bovine enamel exposed to acid solutions after bleaching

Abstract: In vitro evaluation of the microhardness of bovine enamel exposed to acid solutions after bleaching Abstract: Acid erosion is a superficial loss of enamel caused by chemical processes that do not involve bacteria. Intrinsic and extrinsic factors, such as the presence of acid substances in the oral cavity, may cause a pH reduction, thus potentially increasing acid erosion. The aim of this study was to evaluate the microhardness of bleached and unbleached bovine enamel after immersion in a soda beverage, artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
(27 reference statements)
3
15
0
3
Order By: Relevance
“…20 The results of this investigation showed that the dental fragments submitted to bleaching combined with red wine (%SMH red 94.46) and with cola soft drink (%SMH red 92.96) showed higher mineral loss compared to the other groups (Table 1). Higher enamel microhardness values were reported for unbleached teeth compared to the bleached teeth similar to other studies, 7,11 and these were more susceptible to demineralization after contact with acid substances. 7 Thus, the first null hypothesis was rejected.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…20 The results of this investigation showed that the dental fragments submitted to bleaching combined with red wine (%SMH red 94.46) and with cola soft drink (%SMH red 92.96) showed higher mineral loss compared to the other groups (Table 1). Higher enamel microhardness values were reported for unbleached teeth compared to the bleached teeth similar to other studies, 7,11 and these were more susceptible to demineralization after contact with acid substances. 7 Thus, the first null hypothesis was rejected.…”
Section: Discussionsupporting
confidence: 87%
“…2 However, even when obtaining satisfactory clinical results, 3,4 some clinicians have still expressed concerns about the effects of carbamide peroxide bleaching on the oral tissues, which have motivated studies to evaluate the possible adverse effects produced during and after the whitening procedures. [5][6][7] Scientific evidence has shown that enamel can show changes in its structure when exposed to carbamide peroxide affecting its composition and its morphology [8][9][10] and causing surface changes while decreasing the tooth's hardness. 1,11 Greater changes on the enamel surface are observed with the use of acid bleaching products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact may explain the results obtained with regard to pigmentation, since surface roughness and nonuniform geometry can influence the results (CÔRTES et al, 2013). Furthemore, some studies have reported that the acidic pH of pigment solutions promotes a loss of mineral in tooth structure, favoring the penetration of these solutions into the demineralized structure (MESQUITA-GUIMARÃES et al, 2015. ZANET et al, 2011, and others containing ethanol or pigments (BERGER et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…No presente estudo, foi utilizada água destilada, mas, em outras pesquisas, já foram utilizadas solução remineralizante, saliva artificial e saliva humana 12,24 . O meio de armazenagem é muito importante, porque alguns estudos verificaram que a saliva é um contribuinte essencial na recuperação do conteúdo mineral 11,[25][26][27] .…”
Section: Discussionunclassified